What Sparks Entrepreneurial Intentions of Nepalese MBA Students? - Dangol, Jeetendra; Sthapit, Arhan; Chitrakar, Sunil (PYC Nepal Journal of Management, 2024)
This study investigates the influences of personal attitude, subjective norms, and personal behavior control on the entrepreneurial intention of Nepalese MBA students through a structured questionnaire. Using the exploratory factor analysis (EFA) and linear regression equation, this study found that personal attitude and personal behavioral control positively influenced entrepreneurial intention. However, social norms have no explanatory power to influence the students’ entrepreneurial intention. It indicates that the Nepalese MBA students are more interested in establishing their own start-ups or ventures without the influence of any social pressure.